Prospective Exploratory Analysis of Angiogenic Biomarkers in Peripheral Blood in Advanced NSCLC Patients Treated With Bevacizumab Plus Chemotherapy: The ANGIOMET Study - Jantus-Lewintre, Eloisa; Massutí Sureda, Bartomeu; González Larriba, José Luis; Rodríguez-Abreu, Delvys; Juan, Oscar; Blasco, Ana; Dómine, Manuel; Provencio Pulla, Mariano; Garde, Javier; Álvarez, Rosa; Maestu, Inmaculada; Pérez de Carrión, Ramón; et al. (Frontiers in Oncology, 2021)
Finding angiogenic prognostic markers in advanced non-small-cell lung cancer is still an unmet medical need. We explored a set of genetic variants in the VEGF-pathway as potential biomarkers to predict clinical outcomes of patients with non-small-cell lung cancer treated with chemotherapy plus bevacizumab. We prospectively analyzed the relationship between VEGF-pathway components with both pathological and prognostic variables in response to chemotherapy plus bevacizumab in 168 patients with non-squamous non-small-cell lung cancer. Circulating levels of VEGF and VEGFR2, expression of specific endothelial surface markers and single nucleotide polymorphisms in VEGF-pathway genes were analyzed. The primary clinical endpoint was progression-free survival. Secondary endpoints included overall survival and objective tumor response. VEGFR-1 rs9582036 variants AA/AC were associated with increased progression-free survival (p = 0.012 and p = 0.035, respectively), and with improved overall survival (p = 0.019) with respect to CC allele. Patients with VEGF-A rs3025039 harboring allele TT had also reduced mortality risk (p = 0.049) compared with the CC allele. The VEGF-A rs833061 variant was found to be related with response to treatment, with 61.1% of patients harboring the CC allele achieving partial treatment response. High pre-treatment circulating levels of VEGF-A were associated with shorter progression-free survival (p = 0.036). In conclusion, in this prospective study, genetic variants in VEGFR-1 and VEGF-A and plasma levels of VEGF-A were associated with clinical benefit, progression-free survival or overall survival in a cohort of advanced non-squamous non-small-cell lung cancer patients receiving chemotherapy plus antiangiogenic therapy.